The role of graphene oxide precursor morphology in magnetic and microwave absorption properties of nitrogen-doped graphene. (22nd May 2019) - Quan, L; Qin, F X; Estevez, D; Lu, W; Wang, H; Peng, H-X
Abstract: Morphological features, reduction and doping degree of graphene could pose varied effects on its electronic configuration, polarization states, and further trigger of magnetic moments. Herein, three different kinds of graphene oxide (GO) with different corrugations: rippled, folded and flower-like GO in combination with urea were used as precursors to synthesize nitrogen doped graphene (NG) via a facile one-step thermal annealing method to simultaneously achieve nitrogen doping and GO reduction. The magnetic and microwave absorption properties of the three kinds of GO and their corresponding NG were evaluated in terms of structure, C/O ratio (GO reduction degree) and nitrogen doping. The overall results revealed that the reduction is more efficient in the few-layered GO but may be hindered by a folded structure which tends to trap the doped nitrogen atoms. In terms of magnetic properties, flower-like GO and NG with a crumpled structure exhibited the highest magnetization. The NG with a flower-like structure and highest C/O showed the best microwave absorption performance with filling content as low as 10 wt.%, reflected in a reflection loss (RL) of −21.7 dB at 16.8 GHz ( d = 2 mm) and 2.3 GHz of bandwidth. While at the same filling content and absorber thickness, the rippled and folded NGs with lower C/O ratio did not exhibit absorption values of practical application. Thus, higher C/O, proper doping degree and low filler content are required to achieve optimized permittivity and consequently favorable microwave absorbing performance.